A SEMIOTIC ANALYSIS OF TULUDE THE TRADITIONAL CEREMONY OF SANGIHE PEOPLE - Jeane Mangangue (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Tulude is a traditional ceremony which is held by Sangihe people in North Sulawesi. It always celebrated at the end of January. The aim of Tulude celebration is to express gratitude to The Almight God for His protection in the past year.The problem of this study is to identify and classify the meaning of signs in Tulude the traditional ceremony of Sangihe people. The purpose of this study is to describe and analyze the meanings of signs or symbols found in Tulude the traditional ceremony through the objects used in Tulude such as clothing, colours, equipments ,dances and also verbal signs.